(untitled) (Global Journal of Science Frontier Research, 2019)
In this paper we studied the probability distribution associated with sums of sides of any geometric figure indexed in a finite set of Arithmetic Sequence, motivated by the work of researchers in this direction, we derived a probability distribution of an arbitrary sides of geometric figure indexed in a finite set of Arithmetic Sequence with its equivalent recursion form and then give some of its Properties. The results obtained in this paper trivialized and compliment known results in the literatures.